Edukasi Kesehatan Berbasis Pemberdayaan Masyarakat untuk Meningkatkan Kesadaran Bahaya Merokok di Desa Haya-Haya - Hadju, Vidya Avianti; K, Sarinah Basri; Lahay, Sitty Fadhilla Fitrianty (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
Indonesian Health Survey data shows that the number of active smokers reaches 70 million people. Smoking behavior is a risk factor for increasing the prevalence of non-communicable diseases, so efforts to stop cigarette consumption must continue in order to prevent premature death and reduce the prevalence of smoking-related diseases. The objective of this community service initiative is to empower the community in raising awareness about the dangers of smoking through health education in Haya-Haya Village. The method used was observation and analysis of health issues in Haya-Haya Village. Activities included raising awareness among the community about the dangers of smoking, checking blood pressure, and providing educational materials about the dangers of smoking door to door. The three community service activities carried out have a strong synergy in achieving the goal of increasing community awareness about the dangers of smoking. The socialization provides a strong foundation of knowledge, the billboards provide consistent visual reminders, while the door-to-door distribution of stickers ensures the message reaches the family level. This community service activity demonstrates a concrete effort to increase community awareness and knowledge about the negative health impacts of smoking, particularly in Haya-Haya Village.